Kajian Peranan Kontraktor Penyelamat dalam Menyiapkan Projek Pembinaan Terbengkalai - Ismail, Nurfarah Aishah; Sarpin, Norliana; Masrom, Md. Asrul Nasid; Shafii, Haryati; Ismayatim, Norddin (Research in Management of Technology and Business, 2021)
Abandoned construction projects are one of the problems that arise in the construction industry in Malaysia and are becoming increasingly worrying. Therefore, the government have appointed a rescue contractor to complete the abandoned construction project. However, there are a few rescue contractors who are facing challenges in completing the abandoned construction project since the challenges are different from completing regular construction projects. Therefore, the objective of this study is to identify the role and challenges faced by rescue contractors in solving the problems of abandoned construction projects as well as to suggest improvement measures that can be taken by rescue contractors to complete abandoned construction projects. This study uses qualitative methods through interviews with 5 rescue contractors in Selangor, Kuala Lumpur and Johor by interviewing online via e-mail and WhatsApp application. The data analysis was done using content analysis method. The results of the study found that the most important role of the rescue contractor is to complete the project, ensure that the client’s assets can be operated and avoid continuous losses. The challenges for rescue contractors are including work delays, insufficient resources and uncertain cost prices. Meanwhile, the proposed improvement measures are including the rescue contractors need to provide adequate machinery, implement an efficient capital management system, application of Critical Path Method (CPM), hire skilled workers and adequate number of relevant employees and perform work according to the specifications specified in the contract. This study is important to help the rescue contractors in overcoming the problem and thus reducing abandoned construction projects in Malaysia.